2011
DOI: 10.1080/13668803.2011.609658
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the division of household labor outside the family context: utilizing resources for doing gender

Abstract: This study tests alternative theoretical models of the division of household labor within a non-familial context of men and women operating homes for autistic children and adults. This context makes it possible to disentangle overlapping hypotheses that stem from competing models. A sample of 128 staff members completed extensive questionnaires. The analyses yielded considerably different patterns of results for men and women. The results for the men provided support for the relative resources model, showing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
(76 reference statements)
1
2
0
Order By: Relevance
“…However, the mixed findings regarding gender differences in the experience of role conflict (i.e., differences in the experience WIF but not in the experience FIW) are consistent with the results of other studies in the field (Giebels & Janssen, 2004; McElwain, Korabik, & Rosin, 2005) and reflect the changes in gender roles in the contemporary era, which are mainly evident in the area of household tasks (Kulik, 2013). It is possible that because men tend to participate more actively in household tasks today than they did in the past, the interference of family demands with work affects both genders to the same extent (Gaunt & Bouknik, 2012; Goñi-Legaz, Ollo-Lopez, & Bayo-Moriones, 2010), as the findings of the present study revealed.…”
Section: Discussionsupporting
confidence: 47%
“…However, the mixed findings regarding gender differences in the experience of role conflict (i.e., differences in the experience WIF but not in the experience FIW) are consistent with the results of other studies in the field (Giebels & Janssen, 2004; McElwain, Korabik, & Rosin, 2005) and reflect the changes in gender roles in the contemporary era, which are mainly evident in the area of household tasks (Kulik, 2013). It is possible that because men tend to participate more actively in household tasks today than they did in the past, the interference of family demands with work affects both genders to the same extent (Gaunt & Bouknik, 2012; Goñi-Legaz, Ollo-Lopez, & Bayo-Moriones, 2010), as the findings of the present study revealed.…”
Section: Discussionsupporting
confidence: 47%
“…Data from the current study suggest no differences in perceptions of men and women in failure to protect cases. Coupled with shifting views of gender roles (Doucet, 2015; Gaunt & Bouknik, 2012; McLaughlin & Muldoon, 2014), the era of “mother blaming” may be retreating, as fathers seemingly become more culpable in family life. However, while there has undoubtedly been changes in views on gender roles throughout Western society (Kaufman, Bernhardt, & Goldscheider, 2016; Scott, 2006), gendered construction of domestic roles remain largely intransigent to change (McLaughlin, Muldoon, & Moutray, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that these null results reflect a shifting of societal views regarding parenting. Motivated by women’s widespread entry into the labor market, over the last several decades, views regarding the roles of women in family and occupational roles have generally transformed (Doucet, 2015; Gaunt & Bouknik, 2012; McLaughlin & Muldoon, 2014). Consequently, societal expectations of men’s roles in the home and in parenting have also changed (McLaughlin & Muldoon, 2014; Ranson, 2012), suggesting that the modern version of the “good father” is one who is actively engaged in caregiving and involved with his children (Ranson, 2012).…”
Section: Discussionmentioning
confidence: 99%